Features and Functions of the Conserved Herpesvirus Tegument Protein UL11 and Its Binding Partners - Yang, Linjiang; Wang, Mingshu; Cheng, Anchun; Yang, Qiao; Wu, Ying; Huang, Juan; Tian, Bin; Jia, Renyong; Liu, Mafeng; Zhu, Dekang; Chen, Shun; Zhao, Xinxin; et al. (Frontiers in Microbiology, 2022)
The herpesvirus UL11 protein is encoded by the UL11 gene and is a membrane-anchored protein with multiple functions. In the late stage of viral replication, UL11 participates in the secondary envelopment process. It also plays a key role in primary envelopment, transporting newly assembled viral particles through cytoplasmic vesicles and virion egress from the cells processes. UL11 is an important accessory protein and sometimes cooperates with other proteins that participate in viruses-induced cell fusion. Cell fusion is necessary for cell-to-cell transmission. This review summarizes the latest literature and discusses the roles of UL11 in viral assembly, primary and secondary envelopment, and cell-to-cell transmission to obtain a better understanding of the UL11 protein in the life cycle of herpesviruses and for use as a reference for studying other viruses. Additionally, some recently discovered characteristics of UL11 are summarized.